2020
DOI: 10.1101/2020.01.13.899120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DIP/Dpr interactions and the evolutionary design of specificity in protein families

Abstract: AbstractDifferential binding affinities among closely related protein family members underlie many biological phenomena, including cell-cell recognition. Drosophila DIP and Dpr proteins mediate neuronal targeting in the fly through highly specific protein-protein interactions. We show here that DIPs/Dprs segregate into seven specificity subgroups defined by binding preferences between their DIP and Dpr members. We then describe a novel sequence-, stru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…This work was later expanded by a comprehensive set of SPR experiments that quantified DIP/Dpr binding affinities, providing K D values for each interaction and identifying a subset of DIPs that can also engage in homophilic interactions (Cosmanescu et al, 2018). Based on measured binding preferences, phylogenetic profiles, and homology models of complexes derived from available crystal structures, DIPs and Dprs were organized into seven distinct specificity groups so that DIPs and Dprs in one group bind strongly to other proteins within the group but weakly or not at all to DIPs in other groups (Figure 5; Sergeeva et al, 2020).…”
Section: Dips and Dprsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work was later expanded by a comprehensive set of SPR experiments that quantified DIP/Dpr binding affinities, providing K D values for each interaction and identifying a subset of DIPs that can also engage in homophilic interactions (Cosmanescu et al, 2018). Based on measured binding preferences, phylogenetic profiles, and homology models of complexes derived from available crystal structures, DIPs and Dprs were organized into seven distinct specificity groups so that DIPs and Dprs in one group bind strongly to other proteins within the group but weakly or not at all to DIPs in other groups (Figure 5; Sergeeva et al, 2020).…”
Section: Dips and Dprsmentioning
confidence: 99%
“…DIPs and Dprs exhibit more complex specificity patterns (Carrillo et al, 2015;Cosmanescu et al, 2018;Cheng et al, 2019;Sergeeva et al, 2020). Based on the interactome shown in Figure 5, there are a total of 49 possible DIP/Dpr subfamily pairings that can be subdivided into seven ''affinity groups.''…”
Section: Llmentioning
confidence: 99%
See 1 more Smart Citation
“…Each DIP, which has three Ig domains, interacts with a number of Dprs, each of which possesses two Ig domains (176,177); some of these proteins are also capable of homophilic binding (177,178). As DIPs and Dprs show high sequence similarity among each other, specificity of DIP-Dpr interactions appears to be mediated via exclusion/negative constraints (177,179). RNA sequencing (RNAseq) data suggest that DIPs and Dprs are differentially expressed in some corresponding synaptic partners just prior to synaptogenesis (177,178).…”
Section: Circuit Formation and Visual System Developmentmentioning
confidence: 99%
“…10 Such undesirable interactions can, at best, lead to ine ciencies through inhibition, 14 and at worst, result in aggregation 15 or cross-talk between signals. 16 Unwanted interactions can be minimized by designing mismatch between ligands and binding pockets, 17,18 such that deformation costs energy -a form of 'conformational proofreading'. 19 Other work has suggested that residues not directly involved in binding may play a role in discrimination and allostery.…”
Section: Introductionmentioning
confidence: 99%